Antimicrobial Properties of Eco Enzyme: A Literature Review - Pande Ayu Naya Kasih Permatananda; I Gde Suranaya Pandit; Putu Nita Cahyawati; Anak Agung Sri Agung Aryastuti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: In surgical medicine, the use of antimicrobials is very important. The use of antimicrobials or antibiotics is used at the time before surgery as prophylaxis, intraoperative, and postoperative. The prevention of some bacterial infections is imperative. The latest research is constantly evolving toward the use of antibiotics, which follows an increasingly resistant antibiotic trend. One of the advancements in the use of antimicrobials is eco enzymes. Methods: The literatures reviewed in our study was gathered from PubMed and Google Scholar. The advanced search was conducted on PubMed with the keywords used ("Eco enzyme" AND "antimicrobial" AND "activity" OR "Antibiotics"; "Mechanism" OR "Nature"). The advanced search was also conducted on Google Scholar with all of the words "antimicrobial activity of eco enzyme". We reviewed the articles cited within the literature to broaden the search results. Results: Some materials used as eco enzymes in this literature review include Carica papaya L., Annona muricata L., Azadirachta indica Cymbopogon winterianus, Ananas comosus, citrus aurantium, etc. Bioactive substances that play a role in microbacterial activity are flavonoids, tannins, saponins, pH, and lactic acids through mechanisms inhibiting nucleic acid synthesis, inhibit cell membrane function, inhibiting energy metabolism of bacteria, and cross-bacterial cell membranes because of the pH gradient, leading to the disruption of cellular metabolic activities of bacterias. Conclusion: Eco enzymes have been shown to have antimicrobial abilities.